2020 International Conference on Smart Electronics and Communication (ICOSEC) 2020
DOI: 10.1109/icosec49089.2020.9215294
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Artificial Intelligence, Blockchain, Big Data and evolving technologies in Coronavirus Disease - 2019 (COVID-19) curtailment

Abstract: The pandemic of Coronavirus Disease 2019 (COVID-19) is proliferating across the globe obnoxiously and it is the most heard buzzword in recent times. Every person ranging from older people, persons with disabilities, youth, indigenous people have become a part of this chain and are most likely to suffer in the upcoming chronology. S ocial distancing is likely to become a new norm where "Work from Home'', Online Lectures" and "Meetings" ensue on social media applications. Technology has always lent a helping han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Regarding future research trends, the technologies underneath are suggested to enhance robotics research in the intra- and post-pandemic era: AI: AI is expected to be seen in almost every field from household applications to automated robot-assisted health services provided [ 136 ]. Robot applications are suggested to be combined with AI technology towards intelligence and flexibility in the complex working environment [ 106 , 137 ]. The AI algorithms will be an essential support for different areas like data analytics, image processing and decision-making.…”
Section: Discussion and Identification Of Future Research Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding future research trends, the technologies underneath are suggested to enhance robotics research in the intra- and post-pandemic era: AI: AI is expected to be seen in almost every field from household applications to automated robot-assisted health services provided [ 136 ]. Robot applications are suggested to be combined with AI technology towards intelligence and flexibility in the complex working environment [ 106 , 137 ]. The AI algorithms will be an essential support for different areas like data analytics, image processing and decision-making.…”
Section: Discussion and Identification Of Future Research Trendsmentioning
confidence: 99%
“…Peanut robot was utilised for food delivery and medical supply in some cities in China ( Fig. 12 ) [ 106 ]. The robot is beneficial especially in the quarantined area or suspected of the virus.…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…On the other hand, voice robots can assist people who do not use smartphones to complete personal information collection. They use voice recognition to convert the collected personal information into text, and then aggregate it into data [ 214 ]. In addition, the voice robot is also equipped with an intelligent analysis system to help doctors complete remote diagnosis of patients, reducing the possibility of cross-infection between medical staff and patients [ 215 , 216 ].…”
Section: Applications and Impacts Of Digital Technology In Fighting Cmentioning
confidence: 99%
“…For example, the spread of COVID-19 in the city of Wuhan in China raised concerns in other countries about the characteristics of the virus, its impact, as well as determining the countries affected by the epidemic and whether it has been visited by travelers to take preventive measures that limit the spread of infection. This challenge can be overcome by making use of Blockchain technology [ 75 ], which helps in large-scale sharing of information securely by anonymizing patients as well as the verified data.…”
Section: Findings Challenges and Future Directionsmentioning
confidence: 99%